The Impact of Oil Prices on the Food Inflation in Kazakhstan - Baimaganbetov, Sabit; Kelesbayev, Dinmukhamed; Baibosynova, Gulzhan; Yermankulova, Rima; Dandayeva, Botagoz (International Journal of Energy Economics and Policy, 2021)
This paper assesses empirically the effects of real oil price shocks on the food inflation in Kazakhstan for the monthly period 2004-2019 by using a VAR model. Standard unit root tests do not yield reliable results in the presence of breaks. In this regard, Zivot-Andrews (1992) has been tested with the help of unit root test. Food prices have been proven to be I(1) according to the Zivot-Andrews (1992) test, while I(0) is according to the ADF test. In subsequent steps, the causality test of the variables was performed. According to the test, there is a double-chance causality between oil prices and food prices. The short-term effect of the variables is investigated with the help of the VAR model. As a result, crude oil prices have an indirect impact on food prices. Keywords: Kazakhstan, Oil Prices, Food Prices, Inflation, VAR Model, Unit-Root Test JEL Classications: E64, L66, P44, Q41 DOI: https://doi.org/10.32479/ijeep.10844